Kemampuan Guru Akidah Akhlak dalam Melaksanakan Kurikulum 2013 di MTs Swasta Madinatussalam - Neliwati, Neliwati; Ramadhan, M. Rayhan; Adelia, Purnama Sastra; Manungkalit, Khoirunnisa; Ramadhani, Fathis Silmi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This article aims to determine the ability of the Aqidah Akhlak teachers at MTs in implementing the 2013 curriculum at Madinatussalam private MTs. The method used in this study is descriptive qualitative, with data collection techniques through instruments, interviews and triangulation and then simple analysis is carried out. Through this research, it can be seen how much the ability of aqidah akhlak teachers is in implementing the 2013 curriculum learning by looking at the percentage based on achievement indicators and the percentage of respondents. Where the highest percentage based on these indicators can be seen that the teacher has prepared an annual program, semester program, Rpp and KKM. So it can be concluded that the curriculum development that has been carried out at Madinatussalam private MTs can already be carried out properly by looking at the percentage based on achievement indicators and based on respondents. The results of this study can be used as material for recommendations for further research related to the 2013 curriculum with different indicators and places.